Efficacy and safety of pegylated-interferon alpha therapy in patients with chronic hepatitis B in recource-limited settings: A Serbian single-center experience - Bojović, Ksenija; Jordović, Jelena; Simonović Babić, Jasmina; Delić, Dragan; Mitrović, Nikola; Katanić, Nataša (Vojnosanitetski pregled, 2021)
Background/Aim. In Serbia, pegylated interferon (PEG-IFN) alpha-2a has been registered since 2013 for the treatment of patients with chronic hepatitis B (CHB). Numerous advantages, new experiences during the past five years and lack of any published data in our specific population, have initiated this study, with the aim to examine efficacy and safety of PEG-IFN in patients in a Serbian referral center. Methods. This prospective study included 36 patients with CHB who were treated in the Hepatology Department of the Clinic for Infectious and Tropical Diseases, Clinical Center of Serbia in Belgrade, during 2012–2017. Patients had a standard 48-week treatment protocol with PEG-IFN, with measurements of liver enzymes, serology and viraemia before, during, at the end of the treatment and follow-up 6 months afterwards. Treatment outcome was determined using serology (clearance of HBeAg), biochemical [normalization of alanine aminotransferase (ALT)] and virological response [hepatitis B virus (HBV) DNA
Keywords: biochemistry; hepatitis b; antigens; hepatitis b, chronic; peginterferon alfa-2; treatment outcome; virology